Learning preference among accounting students of the University of Mindanao - Barsalote, Clarise C.; Moya, Alyssa Mariztel H.; Sucuahi, William (Technium Social Sciences Journal, 2023)
Learning preferences are a way to enhance the learning experiences. Students can adjust learning processes and techniques if they understand the impact of different experiences. This study utilized cluster analysis to categorize the learning dimensions on the index of learning preferences of first-year accounting students at the University of Mindanao. A survey was conducted on accounting students, and a method of quantitative correlation was employed. Data were collected using a modified research questionnaire. To determine the learning preferences of first-year accounting students, the researchers use gender, age, and socio-economic status as indicators. The statistical treatments used to analyze and interpret data were principal component analysis and clustering analysis. The study's results indicated the following: (a) most students gain the most knowledge from what they hear; (b) the method that the students utilized is Auditory and Visual. In contrast, group and kinesthetic learning preferences are the students' least preferred.